Dominant geaae for awn character in rice (Oryza sativa)" - BHARDWAJ, C; MISHRA, R; SATYAVATHI, C TARA (The Indian Journal of Agricultural Sciences, 2011)
The nature of gene control for awn in altered phenotypes of rice (Oryza savita L.) remains yet to be discerned. An experiment was conducted during the rainy (khar3 seasons 2002-05 to discern the genetic nature of awn character in new plant types. Genetic segregation patterns were observed for awning in 4 generations of the crosses of Jawahar New plant Type (JNPT): 'JNPT 63-01 ' x 'Pusa Basrnati 1' and 'JNPT 89' x 'Pusa Basrnati 1' in parental, F,, F, and F, generations. The observations clearly indicate that awn character in 'Pusa Basrnati 1' is governed by a dominant gene and presence of awn to be dominant over its absence.